2007
DOI: 10.1007/s10753-006-9018-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelins Mediate Neutrophil Activation, ProMMP-9 Release and Endothelial Cell Detachment

Abstract: Neutrophils isolated from human peripheral blood added to a monolayer of human endothelial cells (ECV-304 cell line) stimulated with LPS (100 ng ml(-1)) resulted in: (a) neutrophil activation, measured by spreading and release of leukotriene B(4) (LTB(4)); (b) neutrophil degranulation, measured by release of matrix pro-metalloproteinase-9 (proMMP-9) and (c) loss of the monolayer integrity due to detachment of the endothelial cells. Stimulation of endothelial cells with tumor necrosis factor-alpha (TNF-alpha 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Interestingly, in addition to gedunin effect on neutrophils, it is noteworthy that such limonoid also modulates tEnd.1 cell functions, as observed by diminished adhesion of neutrophils to tEnd.1 monolayers. The mechanisms by which gedunin reduces neutrophil attachment to endothelial cells remains to be investigated; however, it might modulates the expression of adhesion molecules or even the secretion of inflammatory mediators, including ET-1, as previously described by Toffoli and colleagues [ 58 ]. Reduced numbers of lipid bodies observed in gedunin-treated ET-1 stimulated leukocytes corroborates the direct capability of gedunin to modulate leukocyte functions.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, in addition to gedunin effect on neutrophils, it is noteworthy that such limonoid also modulates tEnd.1 cell functions, as observed by diminished adhesion of neutrophils to tEnd.1 monolayers. The mechanisms by which gedunin reduces neutrophil attachment to endothelial cells remains to be investigated; however, it might modulates the expression of adhesion molecules or even the secretion of inflammatory mediators, including ET-1, as previously described by Toffoli and colleagues [ 58 ]. Reduced numbers of lipid bodies observed in gedunin-treated ET-1 stimulated leukocytes corroborates the direct capability of gedunin to modulate leukocyte functions.…”
Section: Resultsmentioning
confidence: 98%
“…LXA 4 decreased in vitro neutrophil chemotaxis, adherence and transmigration across the vascular endothelium and epithelium (McMahon and Godson, 2004; Filep et al ., 2005), CD11b/CD18 expression (Filep et al ., 1999) and blocked superoxide generation (Levy et al ., 1999) and TNF‐α production and actions (Hachicha et al ., 1999). Previous in vitro data demonstrate that ETs cause direct neutrophil activation (Toffoli et al ., 2007), adhesion (Zouki et al ., 1999) and migration in vitro (Elferink and de Koster, 1994). Interestingly, in the present study, we showed that LXA 4 seemed to directly impair ET‐1‐induced neutrophil activation and migration through a mechanism that needs further elucidation.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore the reduction of myeloperoxidase (MPO), a mediator of neutrophil activation (34) and an independent predictor of cardiovascular events (35,36), was more pronounced in patients of the treatment group (▶ Figure 1 A), suggesting that ET-A receptor blockade decreases neutrophil activity which may in turn translate into lower MMP-9 levels. Indeed, it has previously been observed in vitro that pre-incubating neutrophils with BQ-123 leads to a significant reduction of activation and to a decrease in MMP-9 release (17).…”
Section: Discussionmentioning
confidence: 98%
“…ET receptors are found on a broad variety of cells, most importantly on neutrophils which play a crucial role in coronary atherothrombosis (15) and are locally recruited and activated (16). Pre-incubation of neutrophils with an ET-A antagonist decrease subsequent activation (17). Neutrophils mediate the breakdown of extracellular matrix (ECM) mainly by release of matrix metallopeptidase-9 (MMP-9) particularly in the early hours of AMI (18).…”
Section: Introductionmentioning
confidence: 99%